Incidencia y susceptibilidad de enterobacterias causantes de infecciones del tracto urinario en gestantes de 14 a 38 años del Hospital Iquitos "César Garayar García" - Burga Villacis, Cristina Mercedes (2022)
Urinary tract disease is the second cause of infection in humans, occurring more frequently during pregnancy, enterobacteria are the main etiological agents causing these infections, which causes a public health problem as this can affect both maternal health and the fetus, In addition, the inappropriate use of antibiotics generates bacterial resistance, therefore the objective of the research was to determine the incidence and susceptibility of enterobacteria causing urinary tract infections in pregnant women aged 14 to 38 years at the Hospital Iquitos "Cesar Garayar Garcia". A total of 100 urine samples were collected from pregnant women with symptoms of urinary tract infection. Mac Conkey Agar, biochemical tests (Simmons Citrate Agar, TSI Agar, Voges-ProsKauer Broth, Methyl Red Broth, Urea Broth and Hydrogen Sulfide) and susceptibility tests (amikacin, amoxicillin/ac.clavulanic acid, ampicillin/sulbactan, cefepime, imipenem, nitrofurantoin, tetracycline, trimethoprim-sulfamethoxazole) were used. Forty enterobacterial samples were isolated (21 Escherichia coli, 15 Klebsiella sp. and 4 Proteus sp.). High rates of resistance to cefepime were observed in all 3 groups. For Escherichia coli, resistance levels to tetracycline were observed; in Klebsiella sp. and Proteus sp. resistance rates were nitrofurantoin. Likewise, the isolated samples showed high sensitivity to imipenem and amikacin. It was concluded that there was a significant difference (p ? 0.05) in the 3 strains in relation to bacterial sensitivity and resistance and that the incidence of urinary tract infections in pregnant women between 14 and 38 years of age was 40%.